NLRP3 deficiency aggravated DNFB-induced chronic itch by enhancing type 2 immunity IL-4/TSLP-TRPA1 axis in mice - Huang, Si-Ting; Chen, Zuo-Ming; Peng, Zhe; Wang, Yu; Yang, Fan; Tang, Yang; Li, Zi; Wan, Li (Frontiers in Immunology, 2025)
BackgroundThe nod-like receptor family pyrin domain-containing 3 (NLRP3) has been implicated in various skin diseases. However, its role in mediating 2, 4-dinitrofluorobenzene (DNFB)-induced chronic itch remains unclear.MethodsWidetype (WT) and Nlrp3 deletion (Nlrp3-/-)mice, the expression of transient receptor potential (TRP) ankyrin 1 (TRPA1) inhibitor or recombinant mice interleukin-18 (IL-18) were used to establish and evaluate the severity of DNFB-mediated chronic itch. Quantitative real-time PCR, western blotting, immunohistochemistry staining, immunofluorescence staining and enzyme-linked immunosorbent assay (ELISA) was used to examine the expression of NLRP3 inflammasome, type 2 immunity and receptors in dorsal root ganglion (DRG) neurons related with chronic itch. Flow cytometry was performed to quantify the frequency of type 2 immune cells.ResultsThis study revealed that the NLRP3 inflammasome was activated in the skin of DNFB-induced chronic itch mice. Surprisingly, the absence of Nlrp3 exacerbated itch behavior. In Nlrp3-/- mice, IL-18 expression was downregulated, whereas markers of type 2 immunity, such as IL-4 and thymic stromal lymphopoietin (TSLP), were significantly upregulated in the skin. Furthermore, TRPA1 and its colocalization with the IL-4 receptor were increased in the DRG. Inhibition of TRPA1 or administration of recombinant IL-18 significantly reduced DNFB-induced itch behavior in Nlrp3-/- mice. Recombinant IL-18 also decreased the expression of TRPA1, IL-4, and TSLP.DiscussionThese findings suggested that the absence of Nlrp3 aggravated DNFB-induced chronic itch by exacerbating type 2 immunity in the skin and enhancing the IL-4/TSLP-TRPA1 axis, potentially driven by reduced IL-18 levels.